The New Imperial Presidency : Renewing Presidential Power after Watergate. (University of Michigan Press, 2008)
Has the imperial presidency returned? "Well written and, while indispensable for college courses, should appeal beyond academic audiences to anyone interested in how well we govern ourselves. ... I cannot help regarding it as a grand sequel for my own The Imperial Presidency."--Arthur Schlesinger, Jr. Has the imperial presidency returned? This question has been on the minds of many contemporary political observers, as recent American administrations have aimed to consolidate power. In The New Imperial Presidency, Andrew Rudalevige suggests that the congressional framework meant to advise and constrain presidential conduct since Watergate has slowly eroded. Rudalevige describes the evolution of executive power in our separated system of governance. He discusses the abuse of power that prompted what he calls the "resurgence regime" against the imperial presidency and inquires as to how and why--over the three decades that followed Watergate--presidents have regained their standing. Chief executives have always sought to interpret constitutional powers broadly. The ambitious president can choose from an array of strategies for pushing against congressional authority; finding scant resistance, he will attempt to expand executive control. Rudalevige's important and timely work reminds us that the freedoms secured by our system of checks and balances do not proceed automatically but depend on the exertions of public servants and the citizens they serve. His story confirms the importance of the "living Constitution," a tradition of historical experiences overlaying the text of the Constitution itself.